Benefits of living closer to kin vary by genealogical relationship in a territorial mammal. Issue 1990 (11th January 2023) - Walmsley, Sam F.; Boutin, Stan; Dantzer, Ben; Lane, Jeffrey E.; Coltman, David W.; McAdam, Andrew G.
Abstract : While cooperative interactions among kin are a key building block in the societies of group-living species, their importance for species with more variable social environments is unclear. North American red squirrels ( Tamiasciurus hudsonicus ) defend individual territories in dynamic neighbourhoods and are known to benefit from living among familiar conspecifics, but not relatives. However, kin-directed behaviours may be restricted to specific genealogical relationships or strongly mediated by geographical distance, masking their influence at broader scales. Using distance between territories as a proxy for the ability of individuals to interact, we estimated the influence of primary kin (parents, offspring, siblings) on the annual survival and reproductive success of red squirrels. This approach revealed associations between fitness and access to kin, but only for certain genealogical relationships and fitness components. For example, females had enhanced annual survival when living closer to their daughters, though the reverse was not true. Most surprising was the finding that males had higher annual reproductive success when living closer to their father, suggesting possible recognition and cooperation among fathers and sons. Together, these findings point to unexpected nuance in the fitness consequences of kinship dynamics for a species that is territorial and largely solitary.